Refractory hypoxaemia after pneumonectomy: diagnosis by transoesophageal echocardiography. Issue 1 (January 1992) - Berry, L; Braude, S; Hogan, J
Abstract : A patient with normal oxygenation before operation became very breathless and hypoxaemic after a right pneumonectomy. Transoesophageal echocardiography showed right to left interatrial shunting due to a patent foramen ovale. Transoesophageal echocardiography should be included in the assessment of patients who became inappropriately dyspnoeic after pneumonectomy.